2020
DOI: 10.3390/agronomy10071032
|View full text |Cite
|
Sign up to set email alerts
|

Uniparental Inheritance of Salinity Tolerance and Beneficial Phytochemicals in Rice

Abstract: Salinity stress is one of the most problematic constraints to significantly reduce rice productivity. The Saltol QTL (quantitative trait locus) has been known as one among many principal genes/QTLs responsible for salinity tolerance in rice. However, the introgression of the Saltol QTL from the donor (male) into the recipient (female) cultivars induces great recessions from the progeny generation, which results in heavy fieldwork and greater cost and time required for breeding. In this study, the F1 generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…On the other hand, the highest TFC (11.06 mg RE/g DW) was detected in B2, while the lowest TFC (2.54 mg RE/g DW) was found in A2. Previous studies indicated that TPC and TFC increased in rice seedlings under salinity effects [ 38 , 39 , 40 ], which might be due to the upregulation of genes encoding the major biosynthetic enzymes (e.g., phenylalanine ammonia lyase and chalcone synthase) in plant responses to biotic stresses [ 33 , 41 , 42 ]. In this study, TPC and TFC were remarkably stimulated in treatments with 75 mM salinity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the highest TFC (11.06 mg RE/g DW) was detected in B2, while the lowest TFC (2.54 mg RE/g DW) was found in A2. Previous studies indicated that TPC and TFC increased in rice seedlings under salinity effects [ 38 , 39 , 40 ], which might be due to the upregulation of genes encoding the major biosynthetic enzymes (e.g., phenylalanine ammonia lyase and chalcone synthase) in plant responses to biotic stresses [ 33 , 41 , 42 ]. In this study, TPC and TFC were remarkably stimulated in treatments with 75 mM salinity.…”
Section: Resultsmentioning
confidence: 99%
“…This might be due to the differences in genetic diversity among tested rice varieties. In fact, different rice varieties (tolerant and susceptible cultivars) exhibit dissimilar mechanisms in phenolic accumulation to cope with stress conditions [ 33 , 38 , 39 , 40 ]. On the other hand, the present study revealed a notable decrease in the quantities of these phenolics in GBR when exposed to extreme levels of salinity (150 mM).…”
Section: Resultsmentioning
confidence: 99%
“…VP1 / ABI3 plays a significant role during seed development and dormancy inception. , From the mapping population derived from the cross between Osvp1 and Kasalath, Rc partially limited the pigmentation and sprouting of RcRcvp1vp1 progenies (Figure a). This limitation could be a result of uniparental inheritance or maternal effect on pericarp color . First, we identified the red pericarp progenies depended on Rc.…”
Section: Discussionmentioning
confidence: 99%
“…within the cell and is especially responsive at the seedling stage. In the previous study it was found to have the 5 alleles with PIC value of 0.69 20 . In our study the results are comparable with the previous nding and marker RM493 showed 6 alleles with PIC value of 0.72.…”
Section: Discussionmentioning
confidence: 87%